SINTASAN DAN PERTUMBUHAN LARVA CACING NIPAH Namalycastis rhodochorde (POLYCHAETA: NEREIDIDAE) PADA BUDIDAYA DENGAN DUA SUMBER PAKAN BERBEDA - Junardi Junardi; Riyandi Riyandi (Jurnal Akuakultur Rawa Indonesia, 2020)
Nypa Palm Worm Namalycastis rhodohorde has economic potential as an export commodity. Condition current population continues to decline due to habitat degradation and overharvesting. Cultivation be a solution to overcome these problems. On the laboratory scale this species has been successfully cultivated, but still faces obstacles to high mortality in early developmental stages. Larvae obtained by artificial fertilization and maintained with the same stocking density and container as well as the same volume of maintenance media only distinguished by two treated feed. Survival and growth of larvae feed did not differ between treatment seaweed and fermented palm fronds. Different stocking densities suggested for further research related to survival and growth of the Nypa palm worm larvae to obtain the best data for mass production